STRATEGI KEPEMIMPINAN KIAI DALAM MENGEMBANGAKAN PONDOK PESANTREN - Ahmad Taufiq Hidayatullah; Ahmad Faruq; Titin Nurhidayati (PT. Sulthan Journal Publisher, 2026)
Islamic boarding schools in the millennial era face the challenges of globalization and technology, so Kiai need innovative strategies that combine traditional values with modern education without eliminating their Islamic identity. This study examines the leadership strategy of KH Muhsin Bais Suaidi in developing the Miftahul Ulum Al- Azizah Yosorati Sumber Baru Jember Islamic Boarding School. This study uses qualitative research method with phenomenological approach. Data was collected through in-depth interviews, observation, and documentation with a focus on Kiai Ali's leadership and its impact on the development of the Islamic boarding school. The results of this study indicate that there are seven main strategies used by KH Muhsin Bais Suaidi in the development of Miftahul Ulum Al- Azizah Yosorati Islamic Boarding School, namely: realizing the vision and mission of the Islamic Boarding School, strengthening spiritual foundations, building loyalty, developing students'skills, encouraging innovation, improving educational facilities, and establishing external copertion.